SCIENCE BATTLES! : Toto Battle of the Parasite King - Jaehoon, Choi; Yoochul, Lee; Chan, Carmen (Singapore : WS Education, 2023)
"An epic battle is taking place right before our very eyes, noses, ears and mouths! And help is on the way from an unlikely but lovable source. What is this source? Meet Toto, your average boy who takes an extraordinary journey to unpack the fascinating world of viruses, parasites, bacteria and fungi! Become a germs expert and triumph!" --
Originally published as Momui Juineun Naya! Gisaengchung.
Text in English, translated from Korean.
Keywords: Science fiction -- Comic books, strips, etc; Parasite -- Comic books, strips, etc